1977
DOI: 10.1128/jvi.24.2.451-460.1977
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Simian Virus 40 chromatin with Simian Virus 40 T-antigen

Abstract: We have studied the binding of the tumor antigen (T-antigen) of simian virus 40 to simian virus 40 chromatin (minichromosomes). The minichromosomes isolated from infected cells by a modification of standard techniques were relatively free of contaminating RNA and cellular DNA and had a ratio (by weight) of protein to DNA of approximately 1; their DNA was 50 to 60% digestible to an acid-soluble form by staphylococcal nuclease. Cleavage of this chromatin with restriction endonucleases indicated that the nuclease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Furthermore, chromatin with such a distribution of histones should yield equimolar amounts of each limit digest DNA fragment after cleavage by multiple-site restriction enzymes. It should be pointed out that others (11,(41)(42)(43)(44) have presented similar arguments in previous studies on the arrangement of histones in SV40 and polyoma chromatin.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, chromatin with such a distribution of histones should yield equimolar amounts of each limit digest DNA fragment after cleavage by multiple-site restriction enzymes. It should be pointed out that others (11,(41)(42)(43)(44) have presented similar arguments in previous studies on the arrangement of histones in SV40 and polyoma chromatin.…”
Section: Resultssupporting
confidence: 78%
“…The additional 25% which is cleaved upon prolonged incubation suggests that regions presumably near, or perhaps within the nucleosome, are less accessible for cleavage by the enzyme. Importantly, the total susceptible fraction of 50% corresponds well with the estimate of coverage as determined by digestion with nonrestricted endonucleases (8,9,32,41).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Restriction digest analysis of viral DNA. Viral DNA samples were isolated and digested with restriction endonucleases as previously described (13,24). DNA samples of 10 ul contained 1 mg of bromophenol blue per ml, 12.5% glycerol, 2.5% sodium dodecyl sulfate, 50 mM EDTA, and 10 mM Tris-hydrochloride at pH 8.9.…”
Section: Methodsmentioning
confidence: 99%
“…Microinjection of the transcripts from the early strand of SV40 DNA into quiescent mouse kidney cells led to synthesis of SV40 T-antigen, followed by stimulation of cellular DNA synthesis, indicating a causative relationship (19). It was shown that large SV40 T-antigen initiates SV40 DNA replication (20) and negatively controls early SV40 mRNA synthesis (21) and that both events involve the cooperative binding of large SV40 T-antigen to the origin of replication of the viral DNA (22,23). It was reported that large SV40 T-antigen has ATPase activity (24,25), that it interacts with a 53'000 dalton cellular protein (26,27), that it exerts a positive and direct control on the transcription of mammalian ribosomal genes (8,28) and that it positively controls the synthesis of several cellular polyA RNAs (29).…”
Section: Introductionmentioning
confidence: 99%